(untitled) (Research, Society and Development, 2020)
Aging demands specific care for the elderly population, thus, there has been an increase in the number of long-term institutions for the elderly (LSIEs). To improve the health of the elderly, health promotion is essential for the construction of actions that make it possible to meet the social needs of this population, addressing important issues in determining the health-disease process. In this sense, in order to fulfill this demand, an extension project entitled Promotion to the Health of the Elderly (Promid) was developed at the Federal University of Paraná - Campus Toledo, which operated between the years 2017 and 2019 in two care institutions in the city. This report seeks to present the experiencies obtained by the project participants during the execution, on the education and promotion of elderly people health by the use of dialogical and playful approach, presenting the methods that proved to be the most efficient in the LSIEs. For the design of the project, initially, topics relevant to the elderly population and the social context in which they were inserted were listed, the themes were discussed in groups to define the approach strategy. Monthly visits were made to the care institutions, addressing the proposed activities based on playfulness and the dialogic method, combined with an accessible and easily understandable speech, with different forms of approach and teaching materials, always appropriate to the objective of each activity. The execution of the project provided students with the practical application of the knowledge acquired in the academic environment, enabling them to learn about the issue of mourning and encouraging the research of didactic themes and approaches, expanding the horizons of academic knowledge. At the end of the project, there was an enrichment in the development of social skills, interpersonal relationships, in the elderly as well as in the students, evidenced by the better reception of students by the institution and by the elderly during the project.